Securing Rights for Victims A Process Evaluation of the National Crime Victim Law Institute's Victims' Rights Clinics - Davis, Robert C. (RAND Corporation, 2009)
This book discusses how some clinics have won significant gains at the appellate and federal court levels concerning victim standing, the rights to be consulted and heard, and the right to privacy. Some have won significant victories in gaining standing for victims and expanding the definition of particular rights. Others are enjoined in the battle. But all have raised awareness of victims' rights in the justice system.